HOSPITAL BYLAWS SEBAGAI PEDOMAN PENYELESAIAN MASALAH HUKUM DI RUMAH SAKIT: STUDI PADA RUMAH SAKIT UMUM PUSAT PERSAHABATAN - Rini Susanti (2021)
Hospitals as capital-intensive, technology-intensive, and human-intensive institutions in providing complete individual healthcare in the form of outpatient, inpatient, and emergency services have the potential to cause conflict between owners, managers, and medical staff. Hospitals need internal regulations that regulate the relationship between the three elements in the hospital, which are called Hospital bylaws. The preparation and implementation of hospital bylaws are one of the obligations that must be fulfilled by hospitals according to the Law of the Republic of Indonesia No. 44 of 2009 concerning Hospitals. It is also one of the assessments of hospital governance standards in the national standards of hospital accreditation in the Republic of Indonesia. The purpose of this study was to determine the conformity of the hospital bylaws of Persahabatan Hospital with the existing laws and regulations and its compliance to hospital governance standards of Indonesian National Hospital Standards abbreviated as SNARS. It will also seek implementation to hospital bylaws to solve legal problems in the hospital. This research is normative legal research using secondary data. It consists of primary, secondary, and tertiary legal sources. The results of this study proved that the Hospital bylaws of Persahabatan Hospital are in line with the Minister of Health Decree no.772 of 2002 and hospital governance standards of the Indonesian National Standard for Hospitals. However, hospital bylaws as a guideline to the hospital technical operational policy is not consistently referred to, especially in the Director Decree and Standard Operating Procedures in resolution of medicolegal/legal problems.